(untitled) (Tanzania Medical Journal, 2023)
Background Attribution of the anatomical variations of the nose and paranasal sinuses in blockage of osteomeatal complex is an important etiological factor in the pathogenesis of sinus diseases. Functional endoscopic sinus surgery aims to restore the function of the nose and PNS by addressing the natural ostium. However, anatomical variations of the nose and PNS may hamper surgery hence cross-sectional imaging remains to be crucial to operating otorhinolaryngologists. Broad objective This study aimed to characterize anatomical variations of the nose and paranasal sinuses among patients who underwent paranasal sinuses computerized tomography scans at a tertiary hospital in Northern Tanzania. Methodology A descriptive cross-sectional study was conducted at a tertiary hospital, all computerized tomography scan images of patients referred for paranasal sinuses computerized tomography scans were retrieved in axial and multiplanar reformat slices, reviewed by a board-certified radiologist for the presence of anatomical variations. Data were analyzed using the statistical package for social sciences version 20 and summarized in terms of frequencies and proportions for categorical variables. Relationship between independent and dependent variables was established using the Chi-square test where a p-value of <0.05 was considered to be statistically significant. Results There were ninety patients where forty-eight (53.3%) were females and forty-two (46.7%) were males with a mean age of 48.1 ±19.75. years. Of the studied subjects, 81 (90%) had at least one anatomical nose and paranasal sinus variant. The most common variant found in this study was Agger nasi cell 47(52.2%) followed by septal deviation 45(50%) and concha bullosa 44(48.9%). Other variants included Haller cells 14(15.56%) and Onodi cells 10(11.1%), laterally rotated uncinate process 1(1.1%) and dehiscent lamina papyraceae 11(12.2%). Conclusion Anatomical variants of the nose and paranasal sinuses were found to be quite predominant in our hospital setting thus of paramount importance to be well known to otorhinolaryngologists. Each of the anatomical variant has its clinical implication and therefore of significance in management of patients with diseases involving the nose and sinuses.